Enhanced photovoltaic performance of ternary solar cells by doping a new squaraine derivative. (September 2016) - Zhu, Linna; Wang, Rui; Qiao, Jianhui; Wu, Fei
Abstract: Ternary blend solar cells have been proved to be an efficient way to harvest more photons over the near-IR region. In this work, the effect of adding a NIR absorbing squaraine derivative (TPE-SQ) into a conventional P3HT:PC71 BM based bulk heterojunction photovoltaic cell is investigated. The new NIR dye exhibits a quite broad absorption band with full-width at half maximum of 169 nm in the film state, with the absorption edge extending to more than 850 nm. The near infrared absorption of the ternary system is enhanced by the blended squaraine component, and the energy level of the third component matched well with the donor and the acceptor material, leading to increased short-circuit current as well as elevated power conversion efficiency compared to the P3HT:PC71 BM binary solar cell. The highest efficiency of 3.93% is achieved for a P3HT:PC71 BM blend with 2.4 wt % of TPE-SQ. Graphical abstract: A new NIR absorbing squaraine derivative TPE-SQ is synthesized and applied in ternary solar cells. The highest efficiency of 3.93% is achieved for a P3HT:PC71 BM blend with 2.4 wt % of TPE-SQ. Highlights: Squaraine based NIR dye is synthesized and applied in ternary solar cells. The NIR dye exhibits a quite broad absorption band with FWHM of 169 nm. The energy level of the dye matched well with P3HT and PC71 BM. PCE of 3.93% is achieved for a P3HT:PC71 BM blend with 2.4 wt % of TPE-SQ.